Zika virus modulates mitochondrial dynamics, mitophagy, and mitochondria-derived vesicles to facilitate viral replication in trophoblast cells - Lee, Jae Kyung; Shin, Ok Sarah (Frontiers in Immunology, 2023)
Zika virus (ZIKV) remains a global public health threat with the potential risk of a future outbreak. Since viral infections are known to exploit mitochondria-mediated cellular processes, we investigated the effects of ZIKV infection in trophoblast cells in terms of the different mitochondrial quality control pathways that govern mitochondrial integrity and function. Here we demonstrate that ZIKV (PRVABC59) infection of JEG-3 trophoblast cells manipulates mitochondrial dynamics, mitophagy, and formation of mitochondria-derived vesicles (MDVs). Specifically, ZIKV nonstructural protein 4A (NS4A) translocates to the mitochondria, triggers mitochondrial fission and mitophagy, and suppresses mitochondrial associated antiviral protein (MAVS)-mediated type I interferon (IFN) response. Furthermore, proteomics profiling of small extracellular vesicles (sEVs) revealed an enrichment of mitochondrial proteins in sEVs secreted by ZIKV-infected JEG-3 cells, suggesting that MDV formation may also be another mitochondrial quality control mechanism manipulated during placental ZIKV infection. Altogether, our findings highlight the different mitochondrial quality control mechanisms manipulated by ZIKV during infection of placental cells as host immune evasion mechanisms utilized by ZIKV at the placenta to suppress the host antiviral response and facilitate viral infection.